Fuzzy Approach to Statistical Control Charts - Shahryar Sorooshian (Journal of Applied Mathematics)
After investigating the advantages and disadvantages of current methods of statistical process control, it becomes important to overcome the disadvantages and then use the advantages to improve a method for monitoring a process with categorical observations. An approach which considers uncertainty and vagueness is tried for this study; and for this purpose, fuzzy set theory is inevitable to use. So, a new approach based on fuzzy set theory is introduced in this research for monitoring attribute quality characteristics. This approach is then compared with the current related approach to see the difference in performance.